The Influence of OHS Knowledge and Self-Regulation on OHS Compliance (RETRACTED) - Hafidha Tri Kurniati; Kartika Nur Fathiyah (Guidena)
Occupational Health and Safety (OHS) was the most important part of work activity to prevent work-related accidents. Work accidents caused by workers were motivated by the non-compliance of workers in their work. Compliance was a measure for a person to act so that unwanted things do not occur, such as work accidents. OHS Knowledge and self-regulation affected one's compliance to comply with OHS. The purpose of this research was to determine the influence did OHS knowledge (Occupational Health and Safety) and self-regulation had on the compliance of implementing OHS on students who are practicing in chemical laboratories. This research uses a quantitative approach with the research ex-post facto. The research sample used by the method was sampling accidental 80 chemistry students at Yogyakarta State University. The research data collection tools are a compliance questionnaire to apply OHS, self-regulation, and OHS knowledge. The data analysis technique used is the multiple linear regression test. The results showed an effect of OHS knowledge (Occupational Health and Safety) and self-regulation on compliance with applying OHS to students who practice in chemical laboratories (p = 0,000, F = 82,489) with an effective contribution of 68.1%.